Targeted delivery of autoantigen to dendritic cells prevents development of spontaneous uveitis - Klaska, Izabela P.; Yu, Tian; Fordyce, Rosie; Kamoi, Koju; Cornall, Richard J.; Martin-Granados, Cristina; Kuffova, Lucia; Forrester, John V. (Frontiers in Immunology, 2023)
Restoration of immunological tolerance to self antigens has been a major drive in understanding the mechanisms of, and developing new treatments for, autoimmune and autoinflammatory disease. Sessile dendritic cells (DC) are considered the main instruments underpinning immunological tolerance particularly the CD205+ (DEC205+) cDC1 subset in contrast to DCIR2+ cDC2 which mediate immunogenicity. Targeting DC using autoantigen peptide-antibody fusion proteins has been a well explored methodology for inducing tolerance. Here we show that subcutaneous (s.c.) inoculation of hen-egg lysozyme (HEL)-DEC205 Ig fusion prevents the development of spontaneous uveoretinitis (experimental autoimmune uveoretinitis, EAU) in a transgenic mouse model generated by crossing interphotoreceptor retinol binding protein (IRBP)-HEL (sTg HEL) with HEL specific TCR (sTg TCR) mice. Prolonged suppression of EAU required injections of HEL-DEC205 Ig once weekly, reflecting the half life of s.c. DC. Interestingly, HEL-DCIR2 Ig also had a suppressive effect on development of EAU but less so than DEC205 Ig while it had minimal effect on preventing the retinal atrophy associated with EAU. In addition, HEL-DEC205 Ig was only effective when administered s.c. rather than systemically and had no effect on EAU induced by adoptive transfer of HEL-activated T cells. These data demonstrate the importance of systemic (lymph node) rather than local (eye) antigen presentation in the development of EAU as well as suggest a potential therapeutic approach to controlling sight-threatening immune-mediated uveitis provided relevant antigen(s) can be identified.